Pengaruh Model Talking Stick dan Media Audio Visual Terhadap Hasil Belajar Tematik Kelas V - Destini, Frida; Khairani, Fadhilah; Tias, Ika Wulandari Utamining (Didaktika, 2022)
Educators are expected to be able to apply learning models that can motivate students to be more active, responsible, respective and cooperative to others and can improve student learning outcomes. One of the learning models that can be used is the talking stick type cooperative learning model. This research is expected to be able to solve problems related to students' thematic learning outcomes. The purpose of this study was to determine the effect of the talking stick model and audio visual media on the thematic learning outcomes of students. The method used in this study is a quasi-experimental design with a non equivalent control group design. This study uses a saturated sample technique. The instruments used in this study are tests and non-tests, while data analysis uses simple regression tests and multiple regression tests. The results of the study concluded that there was an effect of the application of the talking stick model and audio media on the thematic learning outcomes of students as well as an increase in N-gain of 0.59 in the "Medium". So it is hoped that the application of the talking stick model and audio-visual media to the thematic learning outcomes can be used as a reference for elementary school class teachers